Peningkatan Kompetensi Digital Guru MTs melalui Pelatihan Desain Pembelajaran Interaktif Berbasis Canva - Heridayani Heridayani; Nova Yesyca Naipospos; Suci Dianthiny; Fitri Ani; Prima Yanti Siregar; Leo Benny (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This article presents the outcomes of a Canva-based training program aimed at enhancing the digital competence of teachers at MTs Al-Munawwarah, Kota Binjai, in designing interactive learning media. Implemented through a need-based participatory approach, the workshop emphasized hands-on practice in creating presentation slides, educational posters, and instructional Instagram content. The results indicated significant improvements in participants’ technical skills, visual creativity, and pedagogical awareness. In addition to producing innovative and contextual teaching materials, the training fostered an online learning community to support ongoing mentoring. These findings highlight Canva’s potential as an effective tool for promoting digital transformation in madrasahs and empowering teachers as change agents in technology-integrated education